(untitled) (Research, Society and Development, 2024)
Nursing work is increasingly complex and demanding. In this sense, the development of emotional competencies by nurse managers is crucial as a response to current challenges in health management. This scoping review aims to map the emotional competencies of nurse managers. The scoping review will be carried out according to the guidelines established by the Joanna Briggs Institute and PRISMA-ScR and will include studies on nurse managers’ emotional competencies. Both published and unpublished studies written in english, portuguese or spanish will be considered. When selecting the articles, the duplicates will be removed. The relevance of the titles, abstracts and full texts will be analyzed. Data extraction will be carried out using an instrument previously designed for this purpose, based on the model in the Joanna Briggs Institute Manual. The results will be presented in flowcharts, tables and narrative synthesis. The literature research carried out previously made it possible to identify some of the emotional competencies of nurse managers, such as motivation, empathy and self-control. This review will contribute to identify the emotional competencies of nurse managers.